Genetic features, typification and deflation risk soils on agricultural lands of Belarus - Tsyribka, Viktor; Tsybulka, Mikalai; Alexeichik, Elena; Zhukova, Inna (Journal of the Belarusian State University. Ecology, 2023)
The article describes and presents the groups of soils according to the degree of potential deflation risk. Particle size distribution and structural aggregate composition are the main properties of soils which determine their sustainability to deflation. The typification of lands was carried out depending on the composition of the soil cover, the ratio of its main components. It shows that in sandy loam soils in the structural and aggregate composition, the proportion of deflationary particles is about 75 %, in sandy soils – 90–99 %, in peat soils ranges from 30 to 50 %, and in degraded peat-mineral, mineral residual peat and post-peat - from 50 to 90 %. Sandy soils on heavy sands, peat soils on low-power (0.5–1 m) peat, peat-gley, peat-gley, peat-mineral, underlain by sand, mineral residual peat and post-peat sandy soils have a high degree of deflation risk. Among the deflation risk soils, mineral light soils occupy 86.7 %, peat and degraded peat soils – 13.3 %. Deflation risk lands are most common on the territory of the Belarusian Polesie. In 24 districts, soil areas with a high potential deflation risk occupy more than 50 % of agricultural land. The integral assessment was carried out based on specific gravity indicators in the composition of agricultural lands of deflation risk soils as well as high degree deflation risk soils for a comprehensive assessment of areas according to the degree of deflation risk.
Keywords: deflation risk soils; potential deflation risk; land typification